Stanniocalcin 1 effects on the renal gluconeogenesis pathway in rat and fish. (15th October 2015) - Schein, Vanessa; Kucharski, Luiz C.; Guerreiro, Pedro M.G.; Martins, Tiago Leal; Morgado, Isabel; Power, Deborah M.; Canario, Adelino V.M.; da Silva, Roselis S.M.
Abstract: The mammalian kidney contributes significantly to glucose homeostasis through gluconeogenesis. Considering that stanniocalcin 1 (STC1) regulates ATP production, is synthesized and acts in different cell types of the nephron, the present study hypothesized that STC1 may be implicated in the regulation of gluconeogenesis in the vertebrate kidney. Human STC1 strongly reduced gluconeogenesis from 14 C-glutamine in rat renal medulla (MD) slices but not in renal cortex (CX), nor from 14 C-lactic acid. Total PEPCK activity was markedly reduced by hSTC1 in MD but not in CX. Pck2 (mitochondrial PEPCK isoform) was down-regulated by hSTC1 in MD but not in CX. In fish ( Dicentrarchus labrax ) kidney slices, both STC1-A and -B isoforms decreased gluconeogenesis from 14 C-acid lactic, while STC1-A increased gluconeogenesis from 14 C-glutamine. Overall, our results demonstrate a role for STC1 in the control of glucose synthesis via renal gluconeogenesis in mammals and suggest that it may have a similar role in teleost fishes. Highlights: STC1 inhibited gluconeogenesis from 14 C-glutamine in rat renal medulla. STC1 gluconeogenesis inhibition was absent from rat renal cortex or from 14 C-lactic acid. STC1 inhibited total PEPCK activity in medulla but not cortex. STC1 reduced pck2 in medulla, but not pck1 or in cortex at the lowest concentrations. STC1 also inhibited renal gluconeogenesis from 14 C-lactic acid in a fish.